2019
DOI: 10.1038/s41598-019-56473-0
|View full text |Cite
|
Sign up to set email alerts
|

Applied Precision Cancer Medicine in Neuro-Oncology

Abstract: Brain tumours that are refractory to treatment have a poor prognosis and constitute a major challenge in offering effective treatment strategies. By targeting molecular alterations, precision cancer medicine may be a viable option for the treatment of brain tumours. in this retrospective analysis of our PCM platform, we describe the molecular profiling of primary brain tumours from 50 patients. Tumour samples of the patients were examined by a 161-gene next-generation sequencing panel, immunohistochemistry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…25 In recent years, with the introduction of the concept of precision medicine, molecular targeted therapy for a variety of diseases has become a hot topic. 26 Therefore, basing on precision medicine, exploring the treatment methods of CSCC from the molecular level is expected to improve the current treatment CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…25 In recent years, with the introduction of the concept of precision medicine, molecular targeted therapy for a variety of diseases has become a hot topic. 26 Therefore, basing on precision medicine, exploring the treatment methods of CSCC from the molecular level is expected to improve the current treatment CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Precision cancer medicine targets distinct genetic and epigenetic features of glioma cells to improve disease management and patient survival. [ 26 , 27 ]. In pursuing such a goal, numerous studies and clinical trials have reported several molecular biomarkers as reliable prognostic and predictive factors of high-grade gliomas and newly diagnosed GBM [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the effort to revolutionize treatment should begin from the implementation of a reliable liquid biopsy tool that allows the consistent and noninvasive assessment of tumor status/molecular setup and longitudinal monitoring for changes. 2 , 10 …”
Section: Gbmmentioning
confidence: 99%